2022
DOI: 10.1099/mic.0.001279
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-dependent activity of dapsone against non-replicating persistent mycobacteria

Abstract: One-third of the world’s population is estimated to be latently infected with Mycobacterium tuberculosis . This reservoir of bacteria is largely resistant to antimicrobial treatment that often only targets actively replicating mycobacteria, with current treatment for latent infection revolving around inhibiting the resuscitation event rather than preventing or treating latent infection. As a result, antimicrobials that targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Dapsone in dual or triple combinations with rifampicin, clofazimine, or rifampicin + clofazimine were also effective at eradicating viable Bb. The combinations of dapsone with rifampicin, clofazimine or both are already the therapies of choice to treat multidrug-resistant M. tuberculosis or leprosy (dapsone) and have ample evidence for safety and tolerability in that population (Pattyn, 1990;Seydel et al, 1994;Barr, 2010;Gibson et al, 2022). Furthermore, clinical studies have demonstrated efficacy of dapsone combination therapy in Lyme disease patients with chronic symptoms/PTLD (Horowitz and Freeman, 2019;Horowitz and Freeman, 2020;FIGURE 2 Representative images taken of xenodiagnostic tick midgut smears stained for Borrelia.…”
Section: Treatmentsmentioning
confidence: 99%
“…Dapsone in dual or triple combinations with rifampicin, clofazimine, or rifampicin + clofazimine were also effective at eradicating viable Bb. The combinations of dapsone with rifampicin, clofazimine or both are already the therapies of choice to treat multidrug-resistant M. tuberculosis or leprosy (dapsone) and have ample evidence for safety and tolerability in that population (Pattyn, 1990;Seydel et al, 1994;Barr, 2010;Gibson et al, 2022). Furthermore, clinical studies have demonstrated efficacy of dapsone combination therapy in Lyme disease patients with chronic symptoms/PTLD (Horowitz and Freeman, 2019;Horowitz and Freeman, 2020;FIGURE 2 Representative images taken of xenodiagnostic tick midgut smears stained for Borrelia.…”
Section: Treatmentsmentioning
confidence: 99%
“…Moreover, dapsone, chemically known as 4,4′-diaminodiphenylsulfone, is an old commercially-available widely-used broad-spectrum synthetic sulfone-based antibiotic. 11–19 Dapsone exhibits potent antimicrobial, 20 anti-inflammatory, 21 and antiprotozoal efficacy and is widely employed for the treatment of different skin disorders, such as leprosy and acne, 22 as well as the skin issues that arise in gonorrhea. 18 In addition, dapsone is mainly utilized in the preparation of topical treatments for dermatitis herpetiformis and acne vulgaris.…”
Section: Introductionmentioning
confidence: 99%